2018
DOI: 10.16899/gopctd.366181
|View full text |Cite
|
Sign up to set email alerts
|

Sezaryen doğumun postpartum depresyona ve maternal bağlanmaya etkisi

Abstract: Amaç: Sezaryen ile doğumun postpartum depresyona ve maternal bağlanmaya etkisini incelemek. Gereç ve Yöntem: Sezaryen doğum yapan 90 kadın ve vajinal doğum yapan 90 kadın çalışmaya dahil edilmiştir. Tüm kadınlara postpartum 2. haftada depresif belirtilerinin taranması için Edinburg Doğum Sonrası Depresyon Ölçeği, maternal bağlanmanın değerlendirilmesi için ise Maternal Bağlanma Ölçeği uygulanmıştır. Bulgular: İki grup arasında Edinburg Doğum Sonrası Depresyon Ölçeği ve Maternal Bağlanma Ölçeği ortalama puanlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The study conducted by Şolt-Kırca and Şavaşer 31 (2017) supports this finding and it was stated that maternal attachment did not change according to the type of birth. In the studies of Mutlu et al 32 (2015) and Kokanalı et al 33 (2018), it was declared that maternal attachment was not changed according to the type of birth. In contrast to the results of this study, Egelioğlu-Cetişli et al 21 (2018) and Hergüner et al 20 (2014) found that maternal attachment levels of mothers who delivered vaginally were better than those who delivered by cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Şolt-Kırca and Şavaşer 31 (2017) supports this finding and it was stated that maternal attachment did not change according to the type of birth. In the studies of Mutlu et al 32 (2015) and Kokanalı et al 33 (2018), it was declared that maternal attachment was not changed according to the type of birth. In contrast to the results of this study, Egelioğlu-Cetişli et al 21 (2018) and Hergüner et al 20 (2014) found that maternal attachment levels of mothers who delivered vaginally were better than those who delivered by cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…EPDS is a scale used to assess postpartum depressive symptoms and consists of 10 items. This scale includes statements about how the mother felt during the last week [ 24 ]. Items were designed in a 4-point Likert format.…”
Section: Methodsmentioning
confidence: 99%
“…Postpartum depression is a condition characterized by depressed mood, anxiety, loss of appetite, sleep problems, low energy, and feelings of guilt 2,3 . The prevalence of postpartum depression has been reported to range from 6.7% to 34.8% 4–11 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 The prevalence of postpartum depression has been reported to range from 6.7% to 34.8%. [4][5][6][7][8][9][10][11] Postpartum depression is a leading cause of postpartum morbidity and mortality in women. [4][5][6] It is a serious illness that can lead to suicide or harm to the newborn if left untreated.…”
mentioning
confidence: 99%